Anatomical variations of the lumbrical muscles causing carpal tunnel syndrome - Benny E; Parminder GS; Nur Azuatul AK; Tan, JA; Ahmad Suparno B; Jamari S; Shalimar Abdullah (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Many anatomical variations exist in and around the carpal tunnel. However, symptomatic anomalies causing carpal tunnel syndrome is rare. Additionally, carpal tunnel surgery is considered a simple operation commonly done by junior surgeons who are usually unaware of variations resulting in unfavorable surgical outcomes. We highlight a case of lumbrical muscle variation causing carpal tunnel syndrome. A 73-year-old male presented with numbness and pain of both hands associated with abnormal fullness over both wrists and distal forearms. Initially the right hand was numb and subsequently a year later, the left hand became numb. Physical examination was positive for Durkan, Phalen and Tinel signs at the carpal tunnel. Magnetic Resonance Imaging (MRI) showed abnormal muscle tissues in the carpal tunnel. During the carpal tunnel release and exploratory surgery, we noted an abnormally proximal origin of the lumbrical muscles in the forearm rather than the typical palmar origin. He also had lumbrical muscle hypertrophy in the left side. These two factors resulted in overcrowding within the carpal tunnel. Post-operatively the patient recovered well with pain relief and gradual improvement of his numbness. Variations in the anatomy of the lumbrical muscles is not uncommon and may result in carpal tunnel syndrome. Hence, carpal tunnel release surgeries may not be as straight forward as expected and surgeons should be aware of this possibility.